Hospitalidade e humanização no atendimento odontológico: a percepção dos pacientes - RODRIGUES, Fernando Leonel (2017)
This study aims at analyzing the perception of dental patients in relation to the care provided by dentists highlighting the aspects of hospitality, humanization, quality and service encounter. Its theoretical frame is based upon the SERVQUAL model as well as the Evidence Based Dentistry model (EBD). It establishes a dialogue between the areas of Dentistry, Hospitality, Health Care Humanization, Quality and Service Encounter. The main problem around which the study was developed was: how do patients – either paying themselves for the treatment or through a dental insurance plan - perceive the aspects of hospitality and humanization in their dentist-patient relationship? In order to answer the question, a descriptive and exploratory empirical investigation was carried out. A questionnaire was applied to 342 patients from private practice in the cities of São Paulo and Guarulhos. The responses presented a high internal reliability. Data analysis shows that dental insurance plan patients’ perception of hospitality and humanization is inferior to those of paying patients. In other words, dental insurance plan patients perceive a less hospitable dentist treatment and the dentist-patient trust relationship is weaker.